Soil Settlement Risk From Liquefaction At Lake Toba Tourism Infrastructure, North Sumatera, Indonesia - Hafidzsyah, Rizal (GEOMATE International Society, 2023)
Lake Toba has emerged as a captivating tourist destination in Indonesia, and the government is currently dedicated to enhancing the tourism experience through extensive infrastructure development initiatives. As progress continues, the hazard map for the region notably emphasizes its susceptibility to liquefaction. Therefore, this study aims to evaluate risk of soil settlement arising from potential liquefaction within the Tourism infrastructure of Lake Toba. According to the data collected, it was evident that the prevailing soil layer was dominated by sand and shallow groundwater, rendering it prone to earthquakes, increasing liquefaction potential. Soil settlement was also found in Lake Toba, which further magnified the possibility of liquefaction incidents. The analysis of liquefaction potential was carried out following the empirical method by Idriss-Boulanger (2014) in determining Liquefaction Potential Index (LPI) values. Furthermore, the assessment focused on soil settlement that was observed during instances of liquefaction, by employing methods outlined in Tokimatsu and Seed (1984), Ishihara and Yoshimine (1992), and Cetin (2009). The results showed that the areas exhibited a high liquefaction potential, as evidenced by significantly elevated LPI values. This study centered on settlement reaching up to 1.5 meters during liquefaction events, underscoring the imperative need to implement targeted measures for effective mitigation of this potential hazard.